Studi Kasus: Upaya Pengembangan Kemampuan Kognitif dan Fisik Motorik Pada Anak Tunanetra di Kampus Inklusi - Rachmadina, Alya Rizka; Putri, Fania Amalia; Maheswari, Ken Asti Aura; Kurniawati, Martina Niken; Zarina, Nur Valian Mei; Ummah, Umi Safiul; Harisandi, I GST. Ngurah Putu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This case consider points to investigate procedures and intercessions that can bolster the improvement of cognitive and engine abilities of outwardly disabled children in an comprehensive environment, as well as the challenges confronted in its execution. The case of Marsya Aan Aristin, a young person with add up to visual impairment since the age of one, appears how comprehensive instruction upheld by a multisensory-based approach and focused on preparing can essentially create her cognitive and physical-motor potential. Within the cognitive angle, Marsya was able to illustrate abilities in thinking, foreseeing results, understanding unique concepts, and making categorizations. Within the physical-motor aspect, Marsya's accomplishment in hearing without visual help within the classroom setting gets to be prove that visual restrictions don't ruin her capacity to adjust to the environment. Marsya's victory is the result of a collaboration between comprehensive instruction strategies, educator inclusion, and steady family support. These discoveries emphasize the significance of a all encompassing approach that includes all partners within the improvement handle of children with extraordinary needs.